2000
DOI: 10.1007/s150100050014
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Wound Infection after Herniotomy Associated with Small-Colony Variants of Staphylococcus aureus

Abstract: A small-colony variant (SCV) of Staphylococcus aureus was cultured from a patient with a persistent wound infection (abscess and fistula) 13 months after herniotomy. The strain was nonhemolytic, nonpigmented and grew only anaerobically on Schaedler agar. As it was coagulase-negative, it was initially misidentified as a coagulase-negative Staphylococcus. In further analysis, however, the microorganism was shown to be an auxotroph that reverted to normal growth and morphology in the presence of menadione and hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
48
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 7 publications
1
48
0
1
Order By: Relevance
“…(10). In some small, yet well-documented, case series, the clinical features of chronic infection could be directly related to the SCV phenotype (1,18,25,30,34,35). In addition, some infection models addressed the question of whether SCVs differ in virulence from isolates that show the normal phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(10). In some small, yet well-documented, case series, the clinical features of chronic infection could be directly related to the SCV phenotype (1,18,25,30,34,35). In addition, some infection models addressed the question of whether SCVs differ in virulence from isolates that show the normal phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Further characteristics are (i) altered expression of virulence genes; (ii) intracellular persistence in in vitro systems; (iii) auxotrophism for distinct growth factors, such as thymidine, hemin, and/or menadione; and (iv) the ability to revert to the normal phenotype (16,24). S. aureus SCVs can be particularly isolated in the context of chronic infections, such as osteomyelitis, persistent skin and wound infection, device-related infections, and CF lung disease (1,8,18,25,27,30,34,35). The pathogenesis of S. aureus SCVs in persistent infections is not fully understood, but one recent study has demonstrated the virulence of a site-directed hemin-auxotrophic S. aureus SCV mutant in a murine model of septic arthritis (14).…”
mentioning
confidence: 99%
“…SCVs of S. aureus are important in the pathogenesis of a number of chronic forms of staphylococcal infections, including osteomyelitis (424)(425)(426), relapsing prosthetic joint infection (427,428), skin and soft tissue infection (429), endocarditis (430), and infections involving ventriculoperitoneal shunts (431) and nasal sinuses (432). SCVs are also important in patients with cystic fibrosis (CF) (see Pleuropulmonary Infections, below).…”
Section: Osteomyelitismentioning
confidence: 99%
“…However, the presence of a bacterial subpopulation constituted of small-colony variants (SCVs) is believed to account in part for the increased persistence of the pathogen during chronic or difficult-to-treat infections (1,31,43,48,50). S. aureus SCVs exhibit distinctive phenotypic characteristics on agar, like very small-sized colonies, markedly reduced hemolysin production, and the absence of pigmentation (29).…”
mentioning
confidence: 99%